AIDA Model as a Marketing Strategy to Influence Consumer Buying Interest in the Digital Age - Tristanto, Triyono Adi; Hurriyati, Ratih; Dirgantari, Puspo Dewi; Elyusufi, Abdul Muhaimin (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to analyze the effect of Attention, Interest, Desire and Action models on consumer buying interest as one of the marketing strategies carried out by companies through advertising on Instagram. The analytical method used is multiple linear regression analysis to test the effect of the independent variables on the dependent variable. Attention, Interest and Desire variables have no effect on buying interest where the significance value of each variable is greater than 0.05. Action variable has a significant effect on buying interest where the significance value is 0.041 or less than 0.05.The results of the questionnaire, the Action variable obtained the largest average value in the eighth question, where consumers will buy skin care products as needed. Thus it can be concluded that the skin care products that are in demand by consumers are closely related to the level of consumer needs. Therefore, product innovation is needed according to market or consumer needs. Social media as a means of marketing activities can certainly be the right choice for companies in promoting their skin care products.can provide problem solving solutions to the achievement of a company's marketing activities in the digital era.